2013
DOI: 10.5664/jcsm.2580
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of a Prescription for Bilevel Positive Airway Pressure for Treatment of Obstructive Sleep Apnea among Veterans

Abstract: We identified baseline factors that can help clinicians decide whether to prescribe an auto-BPAP as first-line therapy and that predict good long-term PAP adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…There is mixed evidence regarding the association between disease severity and CPAP adherence, 21,24,34,44,45 and the apneahypopnea index and CPAP pressure are collinear variables. We chose to examine CPAP pressure, as opposed to OSAHS disease severity, for several important reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mixed evidence regarding the association between disease severity and CPAP adherence, 21,24,34,44,45 and the apneahypopnea index and CPAP pressure are collinear variables. We chose to examine CPAP pressure, as opposed to OSAHS disease severity, for several important reasons.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 CPAP pressure setting and OSAHS severity have demonstrated inconsistent relationships with CPAP adherence. [21][22][23][24][25] Positive change in polysomnography (PSG)-measured sleep efficiency from diagnostic study to titration study has been shown to be predictive of better CPAP adherence, 26 so too has higher levels of educational attainment. 27 Psychological predictors of CPAP adherence have demonstrated utility, with individuals who report insomnia symptoms demonstrating poorer adherence, 25,28,29 and anxiety and depression-related symptoms also being predictive of lower levels of CPAP adherence.…”
Section: Brief Summarymentioning
confidence: 99%
“…A recent paper from a Veterans Administration study shows better adherence with bilevel PAP compared with CPAP, but the improvement was almost entirely seen in patients who were older, more obese, had more severe apnea or had concomitant heart failure or COPD [ 13 ].…”
Section: Bilevel Papmentioning
confidence: 99%
“…A study by Schwartz et al . found that improved adherence to BPAP compared to CPAP was largely explained by clinical factors that would predict better suitability for BPAP.…”
mentioning
confidence: 99%